Semaphorin signaling restricts neuronal regeneration in C. elegans - Harreguy, Maria B; Tanvir, Zainab; Shah, Esha; Simprevil, Blandine; Tran, Tracy S; Haspel, Gal (Frontiers in Cell and Developmental Biology, 2022)
Extracellular signaling proteins serve as neuronal growth cone guidance molecules during development and are well positioned to be involved in neuronal regeneration and recovery from injury. Semaphorins and their receptors, the plexins, are a family of conserved proteins involved in development that, in the nervous system, are axonal guidance cues mediating axon pathfinding and synapse formation. The Caenorhabditis elegans genome encodes for three semaphorins and two plexin receptors: the transmembrane semaphorins, SMP-1 and SMP-2, signal through their receptor, PLX-1, while the secreted semaphorin, MAB-20, signals through PLX-2. Here, we evaluate the locomotion behavior of knockout animals missing each of the semaphorins and plexins and the neuronal morphology of plexin knockout animals; we described the cellular expression pattern of the promoters of all plexins in the nervous system of C. elegans; and we evaluated their effect on the regrowth and reconnection of motoneuron neurites and the recovery of locomotion behavior following precise laser microsurgery. Regrowth and reconnection were more prevalent in the absence of each plexin, while recovery of locomotion surpassed regeneration in all genotypes.